Incubation with tau aggregates increases hippocampal circuit excitability and enhances long-term depression in acute mouse hippocampal slices - Wang, Alice; Richardson, Abbie; Emmett, Isabelle; Friedmann, Daniel; Bakker, Saskia; Richardson, Magnus; Hill, Emily; Wall, Mark (Frontiers in Neural Circuits, 2025)
Aggregation of the protein tau is a key pathological hallmark of tauopathies such as Alzheimer’s Disease. Tau dissociates from microtubules and diffuses from the axon into the soma-dendritic compartment, where it aggregates firstly into oligomers and ultimately into neurofibrillary tangles. There is gathering evidence that it is the soluble tau aggregates that are the major active species and that their effects on neuronal electrophysiological properties, synaptic transmission and plasticity could contribute to early cognitive decline. Here we have investigated the effects of incubating acute mouse hippocampal slices with recombinant tau aggregates. We observed interictal events and an increase in excitability of CA3 pyramidal cells. Tau aggregates had little effect on basal synaptic transmission but antagonism of GABAA receptors revealed significant effects of tau aggregates, enhancing the firing of population spikes and the occurrence of bursts following fEPSPs. Tau aggregates produced a concentration-dependent impairment of long-term potentiation (LTP), which could not be overcome by repeated LTP induction stimuli, demonstrating the effects were not just through an elevation of LTP threshold. In contrast to the impairment of LTP, tau aggregates increased G1-mGluR-dependent LTD. Thus, tau aggregates increase hippocampal circuit excitability and shift synaptic plasticity towards depression.